The use and success of cold coagulation for the treatment of high grade squamous cervical intra-epithelial neoplasia: a retrospective review. (August 2016) - McCarthy, C.M.; Ramphul, M.; Madden, M.; Hickey, K.
Abstract: Objective: Cold coagulation is recognised as a viable, cost-effective and successful treatment for cervical intraepithelial neoplasia (CIN), being used less frequently than excisional treatments for high grade lesions. We set out to demonstrate successful long term follow-up of patient with high grade CIN treated with cold coagulation. Study design: We conducted a retrospective review over a one-year period of women with biopsy-proven CIN 2 and 3 who were treated with cold coagulation to the cervix, attending the colposcopy service of a large tertiary referral hospital. We examined follow-up cervical smear data for three years post treatment of low and high grade CIN, evaluated the success of treatment and re-treatment rates. Results: 93 patients were included in our study, with 39 (41.9%) having CIN 1 and 54 (58.1%) diagnosed with CIN 2 or 3. Follow-up smears revealed low levels of recurrent high grade changes in both groups, with 31 (79.5%) of our CIN 1 group having a negative smear one year following treatment with cold coagulation, compared to 44 (81.1%) of patients with CIN 2 and 3. Successful primary treatment (i.e. no requirement for further treatment after 3 year follow-up) occurred in 33 (84.6%) of the CIN 1 group, and 42 (77.7%) of the CIN 2/3 group, demonstrating no statistical significance between re-treatment rates between both groups. Conclusions: This study demonstrates the effectiveness of cold coagulation for the treatment of high grade cervical intraepithelial neoplasia. High success rates, and low re-treatment rates confirm that this is an acceptable primary treatment for CIN 2 and 3.